Phyllostachys danxiashanensis (Poaceae: Bambusoideae), a new species from south China - Zheng, Xi-Rong; Tong, Yi-Hua; Ni, Jing-Bo; Chen, Zai-Xiong; Xia, Nian-He (Phytotaxa, 2019)
A new bamboo species, Phyllostachys danxiashanensis (Poaceae: Bambusoideae), is described from Danxia Mountain, Northern Guangdong. This new species is similar to P. rivalis in having papery culm sheaths, erect culm sheath blades and the absence of culm sheath auricles, but it differs from P. rivalis by its much longer cilia on culm sheath ligules, hispid culm sheaths, and fewer leaves on ultimate branches.